Analisis Budidaya, Pendapatan dan Kelayakan Usaha Lebah Madu Trigona di Desa Kele’i Kecamatan Pamona Timur - Betrin Petuda; Silvany Annatje Taariwuan; Marthen Sangkide (Interdisciplinary Journal (IDe), 2023)
The purpose of this study was to determine and study the cultivation, income and feasibility of trigona honey bee business in Kele'i village, East Pamona District, Poso Regency. The study used a descriptive method. The population in this study is people who cultivate Trigona honey bees with a total of 20 people. Because the trigona honey bee's business is homogeneous, the sample is determined using purposive sampling, namely by deliberately selecting two trigona honey bee cultivators. The data collection method uses interview, observation and documentation techniques. Data analysis in this study was carried out by calculating income and business feasibility. The results showed that the income of trigona honey bee cultivation in Kele'i Village, East Pamona District, from the 2 respondents studied, AL respondents earned income of Rp 3,679,125 and YD respondents earned income of Rp 2,695,667. The results of the feasibility level analysis showed that respondents AL B/C ratio 4.48 obtained a number greater than 1, and respondents YD B/C ratio 2.23. The acquisition of this number is greater than 1 so that the management of trigona honey bee cultivation in Kele'i Village, East Pamona District, is very feasible and very profitable to continue to run and develop.